KẾT QUẢ PHẪU THUẬT ĐỨT GÂN DUỖI VÙNG I CÁC NGÓN TAY TẠI BỆNH VIỆN TRUNG ƯƠNG QUÂN ĐỘI 108 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of surgical repair of zone I extensor tendon injuries of the fingers at 108 Military Central Hospital.Materials and Methods: A cross-sectional descriptive study was conducted on 69 patients who underwent primary repair of zone I extensor tendon injuries at the Department of Upper Limb and Microsurgery, 108 Military Central Hospital, from January 2020 to June 2025. Surgical outcomes were assessed after 6 months using the Miller scoring system.Results: Male patients accounted for 78.3%, mean age 40.6 years. Sports injuries were most common (50.7%). The little finger was most frequently affected (58.0%). No infections were observed. Re-rupture occurred in 10.4%. Good and fair outcomes accounted for 73.9%.Conclusion:  Primary repair provides favorable outcomes and is an effective treatment option.
Keywords: zone I extensor tendon, tendon repair, finger injury, surgical outcome, mallet finger